Relationships, evolution and biogeography of Semaphore geckos, Pristurus (Squamata, Sphaerodactylidae) based on morphology - Arnold, E. N. (Zootaxa, 2009)
The Sphaerodactylid gecko genus Pristurus has at least 20 recognised species in Arabia, the Socotra archipelago, and northeast Africa with an isolate 4500km away in Mauritania. Analysis of nineteen variable morphological characters in the Sphaerodactylidae suggests Pristurus is most closely related to Quedenfeldtia of Morocco and then successively to the Spaerodactylini and Saurodactylus. This contrasts with recent studies using nuclear DNA, which place Pristurus in a basal polychotomy in the family. If the molecular tree is correct, there must have been considerable parallelism in anatomy in these taxa. Within Pristurus, parsimony analysis was carried out on a set of 72 variable morphological characters (equivalent to 86 binary ones) from external features, skeleton, musculature and behaviour. Apparent relationships are as follows: P. celerrimus (P. insignis, P. insignoides) (P. guichardi (P. socotranus (P. abdelkuri (P. rupestris, P. popovi, P. flavipunctatus, P. gallagheri, P. adrarensis, the Spatalura clade)))). Relationships within the Spatalura clade are: (P. minimus, P. simonettai) (P. crucifer, P. phillipsi (P. somalicus (P. saada (P. collaris (P. ornithocephalus, P. carteri))))). The more basal Pristurus were apparently primitively heliothermic rock climbers with one lineage becoming tree dwelling. These forms are now confined to the North Oman mountains of eastern Arabia and the Socotra archipelago and may have been replaced elsewhere in Arabia and perhaps northern Africa by a radiation of more morphologically advanced species. Most of these have similar niches to the more primitive forms, but one lineage that gave rise to the Spatalura clade became ground dwelling and partly nocturnal. Many morphological changes on the phylogeny of Pristurus may be functionally associated with shifts in ecology and behaviour.